2009 IEEE/IFIP International Conference on Dependable Systems &Amp; Networks 2009
DOI: 10.1109/dsn.2009.5270305
|View full text |Cite
|
Sign up to set email alerts
|

Processor reliability enhancement through compiler-directed register file peak temperature reduction

Abstract: Abstract-Each semiconductor technology generation brings us closer to the imminent processor architecture heat wall, with all its associated adverse effects on system performance and reliability. Temperature hotspots not only accelerate the physical failure mechanisms such as electromigration and dielectric breakdown, but furthermore make the system more vulnerable to timing-related intermittent failures. Traditional thermal management techniques suffer from considerable performance overhead as the entire proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…Heat buildup relates closely with the number of accesses to each register. The simulation results in Zhou et al [2008] and Yang and Orailoglu [2009] have confirmed that uniformly distributing register accesses among different registers can effectively reduce the chip-wide peak temperature during program execution. We use Rcount(R x ) to indicate the total number of accesses to a physical register R x .…”
Section: 32supporting
confidence: 79%
See 2 more Smart Citations
“…Heat buildup relates closely with the number of accesses to each register. The simulation results in Zhou et al [2008] and Yang and Orailoglu [2009] have confirmed that uniformly distributing register accesses among different registers can effectively reduce the chip-wide peak temperature during program execution. We use Rcount(R x ) to indicate the total number of accesses to a physical register R x .…”
Section: 32supporting
confidence: 79%
“…(5) The proposed register allocation technique can achieve a reduction of 3.3-6.8 • C in register peak temperature. The peak chip-wide temperature is also reduced by about 3.4-6.6 • C. As discussed in Yang and Orailoglu [2009], even though the amount of temperature reduction seems to be insignificant at first sight, it actually can effectively reduce the fault rate of the entire chip, that is, because previous studies have shown that the fault rate doubles for every 10 • C increase [Lasance 2003], and a large number of delay violations would occur if the peak temperature exceeds 85 • C [Skadron et al 2003]. It can be seen from the results that for most benchmarks, the proposed algorithms can effectively reduce the peak temperature to below 85 • C.…”
Section: Improvement Of Heat Buildup and Temperaturementioning
confidence: 86%
See 1 more Smart Citation
“…Unfortunately, the effectiveness of this approach is limited by design by the use of the NOP instruction, which does not allow the processor to transition from the C0 to the C1E state. We are aware of state-of-the-art compiler-directed techniques to decrease the peak temperature of a processor to improve long-term reliability [18]; however, these techniques target the mitigation of long-term effects like the negative bias temperature instability and the aging.…”
Section: ) Changing the Idle Taskmentioning
confidence: 99%